Formalization as confinement in colonial Hong Kong. (July 2017) - Smart, Alan; Smart, Josephine
The nature of informal economies is structured by conflict between governmental strategies of confinement, to places, times and how things are done, and the transgression of these confines by informal actors in pursuit of survival or advantage. This article examines the influential development program of formalization in the context of these conflicts. Informality can be formalized in two ways, by eradication and by regularization. Building on their past ethnographic research on informality, the authors use released confidential Hong Kong colonial government documents to explore the informal discussions among policy makers about how to respond to informal practices, and how their understanding of street vendors influences their chose of confinement strategies. While insisting on eradication for squatters, various forms of regularization were attempted for street vendors.